HUBUNGAN TINGKAT PENGETAHUAN DENGAN PERILAKU PADA PEROKOK AKTIF DI DESA BONAN DOLOK KABUPATEN HUMBANG HASUNDUTAN [THE RELATIONSHIP BETWEEN KNOWLEDGE LEVEL AND SMOKING BEHAVIOR AMONG ACTIVE SMOKERS IN BONAN DOLOK VILLAGE, HUMBANG HASUNDUTAN DISTRICT] - Dahlia N Hutasoit; Josua Nangkok Panahatan Sinaga; Marolop Natalois; Evanny Indah Manurung; Juwita Fransiska Surbakti (Universitas Pelita Harapan, 2022)
Smoking is a behavior that is detrimental and harmful to health, but this behavior is still difficult to get rid of. The number of smokers worldwide has reached 1.2 billion, and 800 million of them are in developing countries. Smoking has become a culture. The World Health Organization (WHO) notes that currently 36% of Indonesia's population smokes, or more than 60 million people. The aim of this study was to determine the relationship between the level of knowledge and the smoking behavior of active smokers in Bonan Dolok Village, Humbang hasundutan District. This study used a correlational quantitative method to determine the relationship between two research variables. The research test used was the Chi Square test with the condition that if the probability was > 0.05 then Ha's decision was rejected, indicating there was no relationship between the two variables. If the probability < 0.05 then Ha was accepted, meaning that there is a relationship between the two variables The study included 109 samples, obtained through purposive sampling technique. The instrument used in this research is a questionnaire. The results showed that as many as 92 (84.4%) respondents had good knowledge, 57 (52.3%) respondents had poor smoking behavior and there was a relationship between the level of knowledge and smoking behavior in active smokers in Bonan Dolok Village, Humbang Hasundutan District, with p -value 0.00. Future research can dig up more information about other factors that influence smoking behavior such as economics, health status, family or work roles among active smokers in Bonan Dolok Village, Humbang Hasundutan.BAHASA INDONESIA ABSTRAK Merokok merupakan salah satu perilaku yang merugikan dan berbahaya bagi kesehatan, namun perilaku ini masih sulit untuk dihilangkan. Jumlah perokok di seluruh dunia mencapai 1,2 miliar dan 800 juta orang diantaranya berada di negara berkembang. Merokok sudah seperti membudaya, World Health Organization (WHO) mencatat saat ini 36% penduduk Indonesia merokok, atau lebih dari 60 juta orang. Penelitian bertujuan untuk mengetahui hubungan tingkat pengetahuan dengan perilaku perokok aktif di Desa Bonan Dolok Kabupaten Humbang Hasundutan. Penelitian ini menggunakan metode kuantitatif korelasional dengan menggunakan uji Chi-square. Jumlah sampel pada penelitian sebanyak 109 orang yang didapatkan dengan teknik purposive sampling. Instrumen yang digunakan dalam penelitian adalah kuesioner. Hasil penelitian menunjukkan sebanyak sebanyak 92 (84,4%) responden memiliki pengetahuan baik, 57 (52,3%) responden memiliki perilaku merokok kurang baik dan terdapat hubungan antara tingkat pengetahuan dengan perilaku pada perokok aktif di Desa Bonan Dolok Kabupaten Humbang Hasundutan dengan p-value 0,00. Penelitian selanjutnya dapat meneliti faktor-faktor lain yang dapat memengaruhi perilaku merokok.